2011
DOI: 10.1128/jvi.02516-10
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Transient Immune Suppression and the Inhibition of T Cell Proliferation by Type I Interferon

Abstract: Vaccine-induced memory is necessary for protective immunity to pathogens, but many viruses induce a state of transient immune suppression that might contribute to the inability of a vaccine to elicit immunity. We evaluated here the fate of bystander T cells activated by third party cognate antigens during acute viral infections in vivo, using distinct models to track and specifically activate HY and P14 transgenic bystander CD8 T cells in vivo during acute arenavirus infections of mice. Viral infections acted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 48 publications
4
63
0
Order By: Relevance
“…Like many other TLR ligands, poly(I:C) has routinely been used as an adjuvant, but others (33,34) and this study (Fig. 1) have shown that prior exposure to poly(I:C) can inhibit CD8 T-cell responses.…”
Section: Discussionmentioning
confidence: 60%
“…Like many other TLR ligands, poly(I:C) has routinely been used as an adjuvant, but others (33,34) and this study (Fig. 1) have shown that prior exposure to poly(I:C) can inhibit CD8 T-cell responses.…”
Section: Discussionmentioning
confidence: 60%
“…However, cytokine production and migratory potential are only two aspects of a multifaceted T-cell response and the biological relevance of cytokines elicited by heterologous infection can also be ascertained by their influence on other parameters such as proliferation and cytolytic activity. Naïve T-cell proliferation may be inhibited by heterologous infection and/ or type I interferons (35), whereas LCMV-specific memory CD8 + T cells may undergo up to three rounds of proliferation in response to heterologous infection with vesicular stomatitis virus (36) and become actively cytolytic during heterologous vaccinia virus infection (37). Likewise, virus-specific CD4 + T cells initiate their proliferative program more rapidly when exposed to an inflammatory in vivo environment (38).…”
Section: Discussionmentioning
confidence: 99%
“…65 A substantial loss in CD8 and CD4 T cell number during the first 5 days of LCMV infection parallels the levels of type 1 IFN production, does not occur in type 1 IFN receptor ko mice, 66 is blocked by antibody to type 1 IFN 67 and is mimicked by IFN-inducing toll receptor agonists, such as poly I:C. 66 The apoptotic loss of memory occurs prior to cell division. 63,66,68 An in silico virtual immune system model, IMMSIM, which unlike a biological system can selectively turn off either active or passive attrition, predicted that without the active attrition and apoptosis of memory T cells early in infection, crossreactive T cells might overwhelmingly dominate the response to an infection. 61,63 By selectively reducing the frequency of memory cells at the beginning of an immune response, there actually may develop a more diverse T cell response to a new pathogen, and that diversity may be beneficial to the host for control of the pathogen.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%